2019
DOI: 10.1080/13621718.2019.1613010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of corona bond strength of resistance spot welding

Abstract: A simple method to evaluate the strength of corona bond of resistance spot welding is proposed and verified by removing the nugget of welded specimen before conducting a cross tension test. The strength of the corona bond is evaluated using thin steel sheets of different strengths. The result indicates that the higher the strength of the steel sheet, the higher the strength of the corona bond. A tensile test of the corona bond part is conducted using the small tensile test technique to verify the corona bond s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…However, voids were initiated in the UC-HAZ of DP1180-1.0 mm, and a similar prediction has been reported [9]. This change of void initiation position from SC-HAZ (in DP1180-1.4 mm) to UC-HAZ (in DP1180-1.0 mm) is due to the weak bond strength of corona bond in the latter, where corona bond is a pressure-welded part between notch tip and nugget [23]. The void initiation positions in these three DP steels imply that increasing material strength leads to an increase in void initiation angle (Figure 6c), where the definition of void initiation angle is geometrically shown in Figure 6(c).…”
Section: Fe Prediction 2: Applying Gtn Damage Model To Pf Modesupporting
confidence: 81%
“…However, voids were initiated in the UC-HAZ of DP1180-1.0 mm, and a similar prediction has been reported [9]. This change of void initiation position from SC-HAZ (in DP1180-1.4 mm) to UC-HAZ (in DP1180-1.0 mm) is due to the weak bond strength of corona bond in the latter, where corona bond is a pressure-welded part between notch tip and nugget [23]. The void initiation positions in these three DP steels imply that increasing material strength leads to an increase in void initiation angle (Figure 6c), where the definition of void initiation angle is geometrically shown in Figure 6(c).…”
Section: Fe Prediction 2: Applying Gtn Damage Model To Pf Modesupporting
confidence: 81%
“…The nugget part was drilled with a drill of the same size as the nugget diameter, and the test specimens were joined only by the corona bond part. It was confirmed in the previous study [8] that this test can conveniently evaluate the corona bond strength. A cross tensile test was performed with the nugget part perforated.…”
Section: Methodssupporting
confidence: 65%
“…In a previous study [8], we used thin steel sheets of different strengths to remove the nugget of the RSW joint and evaluated the corona bond strength. The CTS of a specimen joined only by the corona bond was approximately 50% of the CTS of a sound RSW joint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those results showed that the corona bond strength could be one of the controlling factors of the fatigue strength of joints. Actually, it has been proved that the corona bond strength was lower than that of nugget by Nakayama 23) and Matsuda 24,25) et al using small tensile specimens sampled from the nugget and corona bond. However, the effect of corona bond on the fatigue strength of RSW joints is not clear.…”
Section: Fatigue Behavior Of Resistance Spot Welded Steel Sheets Fabr...mentioning
confidence: 99%